2014
DOI: 10.1371/journal.pone.0094242
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Children Hospitalized for Parapneumonic Effusion

Abstract: Background & AimsAmong children hospitalized for pneumonia, those with parapneumonic effusion (PPE) are at particular risk for nutritional deterioration. This study aimed to 1) investigate the evolution of the nutritional status during hospitalization and at outpatient follow-up; 2) determine clinical risk factors for weight loss during hospitalization; 3) describe the nutritional interventions for these children.MethodsRetrospective chart review (January ‘07 - September ‘12) of 56 children with pneumonia, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Even in the absence of severe malnutrition, being underweight is associated with an increased risk of pneumonia. 20 A study conducted by Wexler et al in Israel showed that patients with CCAP were often underweight, and this finding is similar to that of our study. However, the result of univariate logistic regression suggests that the condition is not an independent risk factor for CCAP development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even in the absence of severe malnutrition, being underweight is associated with an increased risk of pneumonia. 20 A study conducted by Wexler et al in Israel showed that patients with CCAP were often underweight, and this finding is similar to that of our study. However, the result of univariate logistic regression suggests that the condition is not an independent risk factor for CCAP development.…”
Section: Discussionsupporting
confidence: 92%
“…However, the result of univariate logistic regression suggests that the condition is not an independent risk factor for CCAP development 11 . Our study results are consistent with those reported in the literature 11,20 …”
Section: Discussionsupporting
confidence: 91%
“…A French study, however, reported that a poor nutritional status on admission was not a significant predictor of weight loss (23), which was confirmed in our Belgian study (3). Moreover, in a retrospective study of 56 children with a parapneumonic effusion, children with a higher WFH z score on admission had a more important weight loss in term of percentage during hospitalization (6). We speculated a decreased attention for reduced intake or proper nutritional policy in initially well‐nourished children.…”
Section: Nutritional Status At Admission Versus Nutritional Riskmentioning
confidence: 99%
“…I n the past decade, numerous studies reported undernutrition as a common finding in general (1)(2)(3)(4) and disease-specific pediatric populations (5,6). Systematic nutritional screening has been put forward to timely implement adequate nutritional support and prevent further nutritional deterioration of hospitalized children (7).…”
mentioning
confidence: 99%
“…Independently of the income setting, malnutrition is multifactorial. Whereas malnutrition in low-income countries is often, but not solely, attributable to limited access to food and/or medical care, it is often triggered by disease in in-transition countries [ 5 , 6 ]. Of importance, the report of the Global Burden of Disease Study 2013 revealed that protein-energy malnutrition accounted globally for 9.8/100.000 age-standardized deaths in the largest 50 countries for child and adolescent populations.…”
Section: Introductionmentioning
confidence: 99%